Enchondroma of Tibia as Potential False-positive Finding on 68Ga-DOTATOC PET/CT Scan. (January 2019) - Mahajan, Sonia; Bodei, Lisa; Huicochea Castellanos, Sandra; Grewal, Ravinder K.
Abstract : Abstract: A 70-year-old man with a history of carcinoid tumor of small bowel was referred for 68 Ga-DOTATOC study to evaluate the extent of disease. PET/CT scan revealed known metastatic disease in the liver, with other sites of involvement including pancreas, peritoneum, and bones. In addition, moderately intense uptake was noted in proximal right tibia and further correlation on CT showed metaphyseal lesion with "rings and arcs" calcification suggestive of enchondroma. This case highlights the possibility of overexpression of somatostatin receptors in enchondromas, which has been little explored in literature.